ANALISIS PENGARUH DISIPLIN KERJA TERHADAP KINERJA KARYAWAN F&B DEPARTMENT DI HOTEL THE HERMITAGE JAKARTA - Erika Huang; Sofiani Sofiani (Jurnal Ilmiah Global Education, 2023)
In the study entitled "Analysis of the Influence of Work Discipline on Employee Performance in the F&B Department at The Hermitage Hotel Jakarta", the researcher aims to examine the effect of work discipline on employee performance in the research object. Researchers will identify problems regarding the lack of awareness of some employees about the importance of employee work discipline and there are still employees who come late to work and there are employees who are not in the room during working hours. This research conducted with five dimensions of work discipline to determine the effect on employee performance. This researcher is included in a quantitative study using a sample and a population of employees at a hotel with a total of 70 people. The results of the study show that work discipline has a significant effect on employee performance at The Hermirtage Jakarta Hotel by (0.599) or 59% through the coefficient of determination test. The author's suggestion for The Hermitage Jakarta Hotel is to be able to improve work discipline by re-checking employee attendance so that anyone who is disciplined at work can be detected or not. As well as improving performance even better and being able to maintain performance effectiveness at work.